The Influence of Financial Literacy, Risk Perception, and Investment Behavior on Individual Financial Performance - Adrian Handa; Rina Nopianti; Achmad Choerudin; Muchamad Bachtiar (Journal Management & Economics Review (JUMPER), 2026)
This study aims to analyze the influence of financial literacy, risk perception, and investment behavior on individual financial performance, as well as to examine the mediating role of investment behavior. A quantitative research approach with a causal design was employed, and data were collected through a structured questionnaire distributed to 218 respondents who have experience in financial management and investment activities. The data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to test both direct and indirect relationships among variables. The results indicate that financial literacy and risk perception have positive and significant effects on individual financial performance. Additionally, both variables significantly influence investment behavior, which in turn has the strongest positive effect on financial performance. The mediation analysis further reveals that investment behavior significantly mediates the relationship between financial literacy and financial performance, as well as between risk perception and financial performance. These findings suggest that improving financial knowledge and risk awareness alone is not sufficient; individuals must also adopt appropriate and disciplined investment behavior to achieve optimal financial outcomes. This study contributes to the literature by providing a comprehensive model integrating cognitive, psychological, and behavioral factors in explaining individual financial performance. The results also offer practical implications for policymakers and financial educators in designing effective financial education programs to enhance financial well-being.